Asymmetric Watermarking Scheme Based on Correlation Testing - Rinaldi Munir; Bambang Riyanto; Sarwono Sutikno; Wiseto P. Agung (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2007)
AbstractAsymmetric watermarking is the second generation of watermarking scheme which uses different keys for embedding and detecting watermark. Key for embedding is private or secret, but key for detecting can be available publicly and everyone who has the key can detect watermark Watermark detection does not need to be original multimedia data. Detection of watermark is realized using correlation test between public key and multimedia data received. In most of schemes, private key is the watermark itself; public key is public watermark which correlates to the private watermark This paper presents concept of asymmetric watermarking scheme that based on correlation test and reviews some schemes of asymmetric watermarking that have been proposed by researchers.Keywords: asymmetric watermarking, private key, public key, watermark., multimeelia,:correlation.